2017
DOI: 10.2741/e802
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ancestry on i interleukin-10 i haplotypes in chronic periodontitis

Abstract: Chronic periodontitis is caused by an inflammatory reaction of the periodontal tissues and alveolar bone. This inflammation is caused by periodontopathic bacteria located in the subgingival biofilm, resulting in inflammatory reactions that may lead to loss of attachment. This tissue destruction is a consequence of host immune and inflammatory responses to specific periodontal pathogens and their metabolic products. Cytokines modulate the immune response, altering its efficiency in the competition against patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…Recently, it was found that miRNAs mediated the benefits of exercise and bariatric surgery to the heart in diabetic/prediabetic patients, and the decreased circulating miR-21 were restored after bariatric surgery or physical activity [25, 29]. Moreover, upregulation of miR-21 or downregulation of its targets could lead to diabetic cardiac dysfunction [3032]. Therefore, miR-21 might play important roles in diabetic cardiomyopathy, and it may be a new therapeutic target for metabolic diseases such as T2DM and obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was found that miRNAs mediated the benefits of exercise and bariatric surgery to the heart in diabetic/prediabetic patients, and the decreased circulating miR-21 were restored after bariatric surgery or physical activity [25, 29]. Moreover, upregulation of miR-21 or downregulation of its targets could lead to diabetic cardiac dysfunction [3032]. Therefore, miR-21 might play important roles in diabetic cardiomyopathy, and it may be a new therapeutic target for metabolic diseases such as T2DM and obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Among these studies, 25 studies investigated the ‐1082A>G(rs1800896) polymorphism, 15 studies investigated the ‐819C>T(rs1800871) polymorphism, and 18 studies investigated the ‐592C>A(rs1800872) polymorphism. Nine studies were performed in Asians, 17 in Caucasians, and seven in Latinos. Thirty‐two studies were conducted in systemically healthy subjects and one study in subjects with atherosclerotic and aortic aneurysmal vascular diseases (VD) (VD with CP and VD without CP).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the ‐1082 G allele and GG genotype are associated with high production of IL‐10. And individuals who are high producers of IL‐10 are most likely protected against CP . In addition, significant lower frequencies of GG and AG genotypes were found among CP cases compared to controls that may be considered protective genotypes against susceptibility to CP.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations